The Role of the Principal in Improving Student Discipline and Order: Judad Atwi's Perspective - Nuril Fitria Hidayati; Achmad Muhlis (Responsive: Jurnal Manajemen Pendidikan Islam, 2025)
The principal's role in improving student discipline is crucial for an educational institution. This is because the principal is a key element in improving the quality of education and is directly responsible for managing all educational processes within the school, particularly in efforts to improve student discipline and order. By addressing the topic of the principal's role in improving student discipline and order, the first objective is to understand the principal's position within educational institutions, particularly in efforts to improve student discipline and order. The second objective is to identify strategies implemented by the principal to improve student discipline and order. This study used a literature review method, referring to various books, particularly from Judad Atwi's perspective. From this discussion, it can be concluded that the principal plays a crucial role in education. One of the principal's responsibilities is to discipline students. The success or failure of a school in terms of discipline depends heavily on the principal, as the responsible party. Therefore, he or she plays a significant role in optimally implementing and enforcing these policies. In an effort to increase students' awareness of order and discipline, school principals need to show attention to school regulations and provide rights and obligations to students in accordance with applicable standards and guidelines. Educational institutions function as educational institutions to shape the character of students from various backgrounds. Furthermore, the principal's strategy in improving student discipline is to provide deterrent sanctions for students who violate the rules. The principal has rules and regulations to establish student discipline if a violation occurs, students can be given verbal or written warnings, and can even be fired from school without any charges. It is the student's obligation to obey all the regulations set by the school principal.